Application of GIS as part of flood risk management for evacuation of vulnerable communities during disaster in Kenyir, Terengganu Darul Iman - Norkhairi F.F.; Thiruchelvam S.; Hasini H.; Sidek L.M.; Muda R.S.; Ghazali A.; Mustapha K.N.; Basri H.; Singh R.S.D. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Flood due to the dam break incidence could hardly happen although there are some isolated cases reported around the world. While the probability of the dam to break might be lower, we should be cautious that disaster might strike at any time due to natural or manmade reasons. The flood management plan due to dam break need to be prepared as part of flood risk management which will act as a guideline for the dam owner to manage impending threats. The flood due to dam break could leave catastrophic impact towards the affected area in terms of loss of lives as well as destruction of properties. The usage of geographic information system (GIS) application software in the flood management could assist the dam owner to obtain a clearer picture of the disaster-stricken area should any untoward incidents occur in the future. The GIS data is important in the production of the flood risk management plan. The aim of this study is identify the probable flood risk area by using GIS method. The hydrodynamic data obtained from MIKE-21 will be layered with the image on the Google Earth to obtain the affected area during such flood. The results show that the area that are near to the dam will have high probability to be shattered by the flood. BEIESP.